1975
DOI: 10.1111/j.2153-3490.1975.tb01655.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the carrier gas on the infrared gas analysis of atmospheric CO2

Abstract: Experiments made with different types of infrared gasanalyzers (URAS 1, UNOR 2, UNOR 5B) show considerable deviation in the result when using various mixing ratios of N, and 0, as a "carrier gas" for COP Tellus 135

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…It was replaced with an URAS-2T analyzer in 1974. Since we expected these two analyzers might exhibit different carrier gas responses [Bischof, 1975;Griffith, 1982], the 11 pairs of samples measured with the earlier analyzer were not used in the present analysis.…”
Section: Editing Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It was replaced with an URAS-2T analyzer in 1974. Since we expected these two analyzers might exhibit different carrier gas responses [Bischof, 1975;Griffith, 1982], the 11 pairs of samples measured with the earlier analyzer were not used in the present analysis.…”
Section: Editing Of Datamentioning
confidence: 99%
“…The year-to-year changes of CO2 annual means show considerable variations [Machta et al, 1977]. For the Canadian stations these values range from an actual decrease of 0.6 ppmv (Sable Island, 1976-1975 to an increase of 2.7 ppmv (Sable Island, 1977-1976. The values are consistent among the data sets; the pattern of low and high changes occurs simultaneously at all three stations (Table 7).…”
Section: Long-term Variationsmentioning
confidence: 99%
“…The NDIR gas analyzers indicate erroneous results when the carrier gas composition in the standard gases differs from that in the air sample to be measured (Bischof, 1975;Pearman and Garratt, 1975;Keeling et al, 1976a, b;Pearman, 1977;Griffith, 1982;Griffith et al, 1982). The carrier gas effect arises from the difference in collision-broadened widths of the CO2 absorption lines among different collision partners, and depends on the design of the analyzer, e.g., the absorption band used, the dimension of the sample (or reference) cell and the amount and pressure of CO2 filled in the detector cell.…”
Section: Introductionmentioning
confidence: 99%
“…The carrier gas effect arises from the difference in collision-broadened widths of the CO2 absorption lines among different collision partners, and depends on the design of the analyzer, e.g., the absorption band used, the dimension of the sample (or reference) cell and the amount and pressure of CO2 filled in the detector cell. The standard gases used at all monitoring stations, except for the Stockholm University (Bischof, 1977) which uses CO2-in-air mixtures, are CO2-in-N2 mixtures. Although their concentrations are calibrated against the absolute system of the Scripps Institution of Oceanography (Keeling, 1958), CO2 data obtained at different stations require different corrections for the carrier gas effect properly determined for respective analyzers.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of gas mixtures have been employed for calibration; for example, CO:-air mixtures have been used by Takahashi [1961], and CO:-N: mixtures have been used by Keeling and his co-workers [Pales and Keeling, 1965;Keeling et al, 1965Keeling and Waterman, 1968]. Recently, Bischof [1975] demonstrated that the results of analyses for CO: by infrared gas analyzers (Uras 1, U nor 2, and U nor 5B) are affected by the N:/O: ratio of the carrier gas and that the magnitude of the effect depends upon the type of instrument used. He observed an approximately 1.5% difference in the readings for CO: when pure No.…”
Section: Introductionmentioning
confidence: 99%